Age of Laying Hens Significantly Influences the Content of Nutritionally Vital Lipophilic Compounds in Eggs - Eun-Young Ko; Ramesh Kumar Saini; Young-Soo Keum; Byoung-Ki An (Foods, 2020)
This study aimed to comparatively analyze the carotenoids, tocopherols, fatty acids, and sterols (e.g., cholesterol) in the eggs of laying hens of early (24 weeks), intermediate (42 weeks), and late age (74 weeks), utilizing high-performance liquid chromatography (HPLC), gas chromatography (GC), and GC–mass spectrometry (MS). The results revealed the significantly (p < 0.05) highest content of nutritionally vital compounds (per g of egg yolk, fresh weight), which included (all-E-)-lutein (21.8 µg), (all-E-)-zeaxanthin (13.4 µg), α-tocopherol (76.5 µg), oleic acid (C18:1n9c; 83.3 mg), α-linolenic acid (C18:3n3; 0.68 mg), γ-linolenic acid (C18:3n6; 0.47 mg), arachidonic acid (C20:4n6; 8.11 mg), docosahexaenoic acid (DHA; C22:6n3; 2.06 mg), and total monounsaturated fatty acids (MUFAs; 94.7 mg) and n-3 polyunsaturated fatty acids (PUFAs; 2.74 mg) in the eggs of early-age laying hens compared to intermediate and late-age. Surprisingly, cholesterol was not significantly different in the eggs obtained from the different age groups. In contrast, the fat quality indices, including the lowest atherogenic index (AI) and thrombogenic index (TI) values and high hypocholesterolemic/hypercholesterolemic (h/H) fatty acid ratio, indicated the health-beneficial potential associated with fat intake from the eggs of intermediate and late-age laying hens. Overall, the results of the present investigation suggest that eggs from early-age laying hens can be recommended for a higher intake of antioxidant carotenoids and tocopherols, while the eggs from intermediate and late-age hens can be recommended for the intake of good quality fats.